1966
DOI: 10.1515/zna-1966-0933
|View full text |Cite
|
Sign up to set email alerts
|

Notizen: Der Einfluß eines Magnetfeldes auf die Verbreiterung der Wasserstoff-Linien

Abstract: Hierbei bedeutet

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1969
1969
1995
1995

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The main reason for asymmetries especially in the line center has been shown to be due to the ions and we refer to a recent paper of Sholin [25] which supersedes the earlier papers by Griem [26] and Nguyen-Hoe, Drawin and Herman [27]. In this paper, it has been successfully demonstrated that the observed asymmetries of the Ly-a, H/j-and Hy-lines can all be explained within a static ion approach, where the main effect is caused by the quadrupole term of the ions and to a smaller extent by the quadratic Stark effect and the ion field dependent transition probability corrections of the individual Stark components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason for asymmetries especially in the line center has been shown to be due to the ions and we refer to a recent paper of Sholin [25] which supersedes the earlier papers by Griem [26] and Nguyen-Hoe, Drawin and Herman [27]. In this paper, it has been successfully demonstrated that the observed asymmetries of the Ly-a, H/j-and Hy-lines can all be explained within a static ion approach, where the main effect is caused by the quadrupole term of the ions and to a smaller extent by the quadratic Stark effect and the ion field dependent transition probability corrections of the individual Stark components.…”
Section: Discussionmentioning
confidence: 99%
“…As explained above the program STBRHY may be replaced by the program STBRHY listed at the end for the case of no lower state interactions. Both programs are written in identically the same manner with the only difference that the program STBRHY listed at the end has a simpler matrix ordering and a much simpler and faster calculation of the /(^-matrix according to eq (27), which makes the provision to read in the X-matrix no longer desirable. DIIF(34) CALCULATION OF 3J-SYMB0L.…”
Section: (A3)mentioning
confidence: 99%